Stress Role and Cooping of Working Mothers Living in Tanah Jawa Sub-District, Tanah Jawa District, Simalungun Regency - Beta Hanindiya; Damanik, Nurasima Kurniati (PT Inovasi Pratama Internasional, 2023)
Stress is a disturbance to the body and mind caused by a discrepancy between the demands received and the ability to overcome them. One source of stress is the demand to carry out two roles simultaneously, for example in working housewives. While coping is a way that is done by individuals in solving problems, adjusting to change. Coping is divided into two, namely those that focus on problems and those that focus on emotions. This study aims to identify the role stress and coping used by working mothers using a descriptive design. The samples taken were 80 women working in the Tanah Jawa Village, Tanah Jawa District, Simalungun Regency using a purposive sampling technique. The results showed that the stress of working mothers who lived in Tanah Jawa Village, Tanah Jawa District, Simalungun Regency was light, namely 93.8% because the majority of working hours of mothers in Tanah Jawa Village were relatively short, namely 5 hours a day, and experienced stress. role as household manager (Mean = 2.64 and SD = 2.076). And the coping used in this study is coping that focuses on problems (Mean = 21.19 and SD = 3.66) while coping that focuses on emotions (Mean = 14.23 and SD = 4.41). It can be concluded that mothers who work in the Tanah Jawa sub-district use more problem-focused coping. This is related to the mother's knowledge and personality. For further research it is recommended to conduct research on 2 other roles, namely as caregivers and workers.